Pedicle transfer in oral cavity reconstruction - Yadav Prabha; Ahmad Quazi; Shankhdhar Vinay; Nambi G (Indian Journal of Plastic Surgery)
In head and neck reconstructions when a free flap is used intra orally to provide the lining its vascular pedicle has to be transferred to the neck for anastomosis. This has to be performed in such a way that the pedicle does not get kinked or twisted. The pedicle is enrolled in a split open glove from its point of entry into the flap till its proximal most part. In order to prevent twisting of the vessels and to maintain orientation, the glove is wrapped in such a way that the imprint on the glove is on the visualized surface. The glove wrapped pedicle is passed from inside the oral cavity while an artery clamp passed from the neck wound through the submandibular or subcutaneous tunnel holds the tip of the glove component and guides it safely to the neck without exerting any traction on the flap or the pedicle vessels.